Analisa Segmen Penumpang Angkutan Udara Niaga Berjadwal Dalam Negeri - Yuliana, Dina; Rizki, Yuke Sri (Warta Penelitian Perhubungan, 2010)
Air transport business in Indonesia is undergoing rapid changed, the cxmqrition is rery high rehreenthe national air transport companies. The research used descriptire statistics and Kruskal - Wallis test,The results showed that PT.Garuda Indonesia Airlines passenger the most widely journetj in orderbusiness (52.4%) with m;erage inromes above 10 million rupiah (78.2%), PT. lion Air passengerjournetj fur the purpose official. task (27.1%) due to lower prices (32.4%). PT. Batavia Air passengerjournetj fur the purpose of school I studies (40.7%) due to ease of getting tickets (36.5% ), PT. MandalaAir passenger journey fur the social and family purposes (21.5%) with arerage inromes are lower than2 million (14 % ), and PT. Sriwijaya Air passenger journey fur social purpose return home, and otkrs. (91.7%) and reasons fur choosing the airline because the provided services (28.2%).